Research Trends in Critical Thinking: Bibliometric Analysis Using VosViewer (1994–2023) - Yaktiva Dwi Purnama (Scientia Publica Media, 2024)
Critical thinking skills have emerged as a prominent aspect of 21st-century competencies over the past three decades. The authors have shown a growing interest in investigating these skills in recent years. This research employs bibliometric analysis through the VOSviewer application, spanning the period from 1994 to 2023, to scrutinize the current trends and status of critical thinking skills research. Utilizing Scopus data, a total of 16,011 journal articles were considered for bibliometric mapping analysis. The findings reveal that in 2022, there is a peak of publications is 1602. The most commonly used keywords include critical thinking, education, and higher education. Noteworthy papers by Anderson T. et al., Andrews-Hanna J.R. et al., and Carini R.M are identified as the most frequently cited documents. Prolific authors such as Hwang, Pascarella, and Oxman are highlighted, and journals like Nurse Education Today, Thinking Skills and Creativity, and Journal of Nursing Education stand out. Leading institutions include the University of Toronto, State University of Malang, and Monash University, while the most active countries in this field are the US, UK, and Australia. The findings from the science mapping reveal an increasing focus on the development of critical thinking abilities, particularly within the realms of Health and Education. This indicates that the subject is likely to remain a prominent discussion point in the future, given its significance in enhancing both work quality and educational standards.